Penentuan Jenis Kondisi Luminansi Langit dengan Rasio Awan dan Data Lama Penyinaran Matahari di Makassar - Husni Kuruseng; Muhammad Ramli Rahim (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2018)
This study was evaluated the results of the measurement data from the global light (global illuminance) and diffuse light/reflection (diffuse illuminance), and the sunshine duration in Makassar which become essential components used in various calculations and daylight applications in buildings. Total days of measurement as much as 143 days with the amount of data recorded on as many as 6971 global luminance data (Evg). Daily data processing done for each month of measurement that indicates the data recorded every 15 minutes. Furthermore, every day is equipped with a measurement of each image fluctuations of daily data for a global luminance (Evg) and diffuse (Evg). The results obtained by the number of quality control of data quality control results for the Evg data 6970 or 99.99% of the total data recorded as many as 6971 data. The results of quality control data for 6971 Evd data or 100% of the total data recorded as many as 6971 data. The results of quality control comparison of global luminance data (Evg) and diffuse (Evd) shows the result of 93.44% of the data that pass quality control or as many as 6.499 data from the 6.971 recorded data. Quality control results do show that the results of measurements of global and diffuse luminance held in Makassar in 2010 and is a qualified data that is valid for further analysis under guidelines of the CIE-IDMP. The collected sunshine duration data which include monthly data for the years 1995-2010. From the 16 years of data collected, the average sunshine duration in Makassar was 68% with the highest monthly average by 88% in August and the lowest by 44% in December. The results of the analysis of sky condition by cloud ratio and sunshine duration data methods are relative similar.